Effects of the nitrification inhibitor nitrapyrin and the plant growth regulator gibberellic acid on yield-scale nitrous oxide emission in maize fields under hot climatic conditions - Dawar, Khadim (2021)
Nitrification inhibitors are widely used in agriculture to mitigate nitrous oxide (N2O) emission and increase crop yield. However, no concrete information on their mitigation of N2O emission is available under soil and environmental conditions as in Pakistan. A field experiment was established using a silt clay loam soil from Peshawar, Pakistan, to study the effect of urea applied in combination with a nitrification inhibitor, nitrapyrin (2-chloro-6-tri-chloromethyl pyridine), and/or a plant growth regulator, gibberellic acid (GA3), on N2O emission and the nitrogen (N) uptake efficiency of maize. The experimental design was a randomized complete block with five treatments in four replicates: control with no N (CK), urea (200 kg N ha–1) alone, urea in combination with nitrapyrin (700 g ha–1), urea in combination with GA3 (60 g ha–1), and urea in combination with nitrapyrin and GA3. The N2O emission, yield, N response efficiency, and total N uptake were measured during the experimental period. The treatment with urea and nitrapyrin reduced total N2O emission by 39%–43% and decreased yield-scaled N2O emission by 47%–52%, relative to the treatment with urea alone. The maize plant biomass, grain yield, and total N uptake increased significantly by 23%, 17%, and 15%, respectively, in the treatment with urea and nitrapyrin, relative to the treatment with urea alone, which was possibly due to N saving, lower N loss, and increased N uptake in the form of ammonium; they were further enhanced in the treatment with urea, nitrapyrin, and GA3 by 27%, 36%, and 25%, respectively, probably because of the stimulating effect of GA3 on plant growth and development and the reduction in biotic and abiotic stresses. These results suggest that applying urea in combination with nitrapyrin and GA3 has the potential to mitigate N2O emission, improve N response efficiency, and increase maize yield.